The Relationship Of Knowledge, Family Support And Support Of Health Officers With Exclusive Breastfeeding On Babies Aged 7 – 12 Months At The Puskesmas Sukajadi, Banyuasin Regency In 2021 - Depri Yunita Sari; Siti Aisyah Hamid; Erma Puspita Sari (Institute of Computer Science (IOCS), 2022)
Exclusive breastfeeding according to the World Health Organization (WHO) is only giving breast milk to babies, not giving additional in any form from the age of 0-6 months. Infants who are not exclusively breastfed have a 3.94 times greater risk of dying from diarrhea than those who are exclusively breastfed and babies who are not exclusively breastfed are prone to respiratory infections and gastrointestinal infections that are higher than those who are exclusively breastfed. In addition, babies who are not exclusively breastfed are susceptible to diseases related to immunity. This study aims to determine the relationship between knowledge, family support and support from health workers with exclusive breastfeeding for infants aged 7-12 months at the Sukajadi Health Center, Banyuasin Regency in 2021. The method in this study used a cross sectional with a population of 45 respondents and a sample of 45 respondents using purposive sampling technique. Data analysis used chi square statistical test with p value value (0.05). The results of this study were from 15 respondents with good knowledge who received exclusive breastfeeding (73.3%) with p value = 0.02, meaning that there was a relationship between knowledge and exclusive breastfeeding, from 23 respondents with family support who received exclusive breastfeeding (76 ,2%) obtained p value = 0.001, meaning that there is a relationship between family support and exclusive breastfeeding with exclusive breastfeeding for infants aged 7-12 months and 23 respondents with the support of health workers who received exclusive breastfeeding (65.2%) obtained p-value = 0.02. This means that there is a relationship between health workers and exclusive breastfeeding. From this study, it can be concluded that there is a simultaneous relationship between knowledge, family support and health care workers' support for the provision of exclusive breastfeeding to infants aged 7-12 months at the Sukajadi Health Center, Banyuasin Regency in 2021. Midwives are expected to further improve services and education for exclusive breastfeeding mothers. to people who have babies aged 7-12 months. Midwives are expected to further improve services and education for exclusive breastfeeding mothers. to people who have babies aged 7-12 months. Midwives are expected to further improve services and education for exclusive breastfeeding mothers. to people who have babies aged 7-12 months